2014
DOI: 10.1037/a0031661
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing health consequences of Hurricane Katrina from the perspective of socioeconomic status decline.

Abstract: Objective The long-term health impact of acute unemployment and socioeconomic resource deficit has not been shown to be unique from the effects of stable socioeconomic status (SES) and serious life circumstances, such as trauma. This study examined associations between these acute socioeconomic declines and health of hurricane survivors, independent of prehurricane SES and hurricane trauma. Method Participants were 215 African American adults (60% female, mean age = 39 years) living in the Greater New Orlean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…We also hypothesized that, consistent with the COR theory and some other studies (16), that resource deficit would partly account for associations between hurricane experience and birth outcomes. Our results, though, would suggest that the initial hurricane experience and ongoing hurricane-related worry were most important in predicting outcomes, as the results were not consistent with substantial mediation by current socioeconomic resource deficit.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We also hypothesized that, consistent with the COR theory and some other studies (16), that resource deficit would partly account for associations between hurricane experience and birth outcomes. Our results, though, would suggest that the initial hurricane experience and ongoing hurricane-related worry were most important in predicting outcomes, as the results were not consistent with substantial mediation by current socioeconomic resource deficit.…”
Section: Discussionsupporting
confidence: 54%
“…Long-term socioeconomic decline and socioeconomic resource deficit were associated with cardiometabolic events and pain 4 years after Hurricane Katrina, even after the initial experience of the hurricane was taken into account (16). A study done 3 years after the Wenchuan earthquake found high levels of chronic disease and low quality of life (17).…”
Section: Introductionmentioning
confidence: 99%
“…One possible mediator is social support; relative to those who have returned to their predisaster homes and communities, those who have relocated or lived in unstable housing are likely to have lost contact with more members of their social support networks, increasing risk for mental health problems (e.g., Kaniasty & Norris, 2009). Other potential mediators are unemployment, financial loss, and child psychopathology, each of which is more likely among the displaced and each of which has been shown to increase mental health risks (e.g., Joseph, Matthews, & Myers, 2013; Scheeringa & Zeanah, 2008). COR theory could be explored with qualitative studies exploring participants’ lived experiences of displacement could provide insight into how these or other stressors associated with relocation and unstable housing lead to poor psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while most attention to climate change and poverty mechanisms focuses on the developing world, there is also a need for exploration of climate-related reductions in income within the developed world. Within the United States, for example, socio-economic stress resulting from Hurricane Katrina has had persistent effects on the health status of otherwise vulnerable populations, 188 which may have significant long-term poverty implications. It is likely that Hurricane Sandy, which damaged or destroyed more than 650,000 housing units in the US Northeast, 189 will also contribute to increased poverty, particularly for lower-income households who experienced major damage to their homes and did not have flood insurance coverage.…”
Section: Conclusion: Priorities For Future Researchmentioning
confidence: 99%